Granulocyte–macrophage colony-stimulating factor expression in induced sputum and bronchial mucosa in asthma and COPD. Issue 8 (12th February 2009) - Saha, S; Doe, C; Mistry, V; Siddiqui, S; Parker, D; Sleeman, M; Cohen, E S; Brightling, C E
Abstract : Background: Granulocyte–macrophage colony-stimulating factor (GM-CSF) has been implicated as an important mediator in the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD). However, the expression of GM-CSF and its receptor in airway samples in asthma and COPD across disease severity needs to be further defined. Methods: Sputum GM-CSF was measured in 18 control subjects, 45 subjects with asthma and 47 subjects with COPD. Enumeration of GM-CSF+ cells in the bronchial submucosa and airway smooth muscle bundle was performed in 29 control subjects, 36 subjects with asthma and 10 subjects with COPD. Results: The proportion of subjects with measurable GM-CSF in the sputum was raised in those with moderate (7/14) and severe (11/18) asthma, and in those with COPD GOLD (Global Initiative for Chronic Obstructive Lung Disease) stage II (7/16), III (8/17) and IV (7/14) compared with controls (1/18) and those with mild asthma (0/13); p = 0.001. The sputum GM-CSF concentration was correlated with the sputum eosinophilia in subjects with moderate to severe asthma (rs  = 0.41; p = 0.018). The median (interquartile range) GM-CSF+ and GM-CSFR+ cells/mm 2 of submucosa was increased in severe asthma (1.4 (3.0) and 2.1 (8.4)) compared with those with mild to moderate asthma (0 (2.5) and 1.1 (5)) and healthy controls (0 (0.5) and 0 (1.6)), (p = 0.004 and p = 0.02, respectively). Conclusions: The findings support a potential role for GM-CSF in asthma and COPD and suggest that overexpression of GM-CSF in sputum and the bronchial mucosa is a particular feature of severe asthma.